The complete plastid genome sequence of Vaccinium japonicum (Ericales: Ericaceae), a deciduous broad-leaved shrub endemic to East Asia - Won-Bum Cho; Eun-Kyeong Han; In-Su Choi; Dong Chan Son; Gyu Young Chung; Jung-Hyun Lee (Mitochondrial DNA. Part B. Resources, 2021)
We here sequenced the complete plastid genome (plastome) of Vaccinium japonicum (Ericaceae), a deciduous broad-leaved shrub endemic to East Asia. This species has considerable practical economic value. The plastome of V. japonicum is assembled as a single contig (187,213 bp). A large single copy (104,637 bp) and a small single copy (3,000 bp) of the genome are separated by a pair of inverted repeats (39,788 bp). The genome consists of 135 genes, which include 88 protein coding, eight ribosomal RNA, and 39 transfer RNA genes. The plastome of V. japonicum is similar to that of Vaccinium macrocarpon in gene content and order. Our phylogenetic analysis revealed the phylogenetic position of V. japonicum in a highly supported clade of the genus Vaccinium together with other four congeners, V. bracteatum, V. vitis-idaea, V. uliginosum and V. macrocarpon.